Analisis terhadap Aksesibilitas Lingkungan Fisik untuk Mahasiwa Disabilitas di Universitas Sultan Ageng Tirtayasa - Asmiati, Neti; Abadi, Reza Febri; Mulia, Dedi (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
The purpose of this study was to analyze the accessibility of the physical environment for students with disabilities at Ageng Tirtayasa university. To support the activities of disabled students on campus, of course, universities must provide accessible facilities and infrastructure for students with disabilities. This study uses descriptive qualitative methods, broadly this research goes through 3 stages and this research will be carried out at Sultan Ageng Tirtayasa University with research informants 2 policy makers at the university and faculty level, 3 students with disabilities where the results obtained from this study are Sultan Ageng Tirtayasa University has provided physical accessibility facilities for students with disabilities such as guaiding blocks, ramps and hand trails, lifts in the new building and access to classes on the ground floor for students with disabilities in the old building. However, the provision of this accessibility is still not optimal, but until now the University of Sultan Ageng Tirtayasa continues to strive to provide accessibility according to standards in new buildings which are still in progress.